Mapping Research Problematika Zakat Indonesia Di Era Society 5.0: Systematic literature review-VOSviewer - Muhammad Sultan Mubarok (LPMP Imperium, 2022)
This study aims to discuss the development of research related to zakat problems in Indonesia over the past ten years (2011-2021). Based on research using the SLR-Vosviewer method, it was found that ISRA International Journal of Islamic Finance is the journal with the highest impact factor or significance level with the Scopus Q3 category and its SJR of 0.345. The most widely used keywords in zakat journals are themed Zakat Management, while the keyword clusters are divided into 24 clusters. Finally, the latest zakat research links zakat and asymmetric information, bureaucracy, and efficiency. This study limited the sample to only journals indexed by Scopus, Sinta 1, and Sinta 2. The significance of the research lies in the SLR-Vosviewer method as a bibliometric analysis tool for the zakat challenge